Using pneumococcal carriage studies to monitor vaccine impact in low- and middle-income countries. Issue 43 (8th October 2019) - Chan, Jocelyn; Nguyen, Cattram D.; Dunne, Eileen M.; Kim Mulholland, E.; Mungun, Tuya; Pomat, William S.; Rafai, Eric; Satzke, Catherine; Weinberger, Daniel M.; Russell, Fiona M.
Abstract: Pneumococcal disease is a leading cause of childhood mortality, globally. The pneumococcal conjugate vaccine (PCV) has been introduced to many countries worldwide. However there are few studies evaluating PCV impacts in low- and middle-income countries (LMIC) because measuring the impact of PCV on pneumococcal disease in LMICs is challenging. We review the role of pneumococcal carriage studies for the evaluation of PCVs in LMICs and discuss optimal methods for conducting these studies. Fifteen carriage studies from 13 LMICs quantified the effects of PCV on carriage, and identified replacement carriage serotypes in the post-PCV era. Ten studies reported on the indirect effects of PCV on carriage. Results can be used to inform cost-effectiveness evaluations, guide policy decisions on dosing and product, and monitor equity in program implementation. Critically, we highlight gaps in our understanding of serotype replacement disease in LMICs and identify priorities for research to address this gap.